Ensino religioso no contexto escolar : educação em valores - Matos, Rita Estefânia Luz dos Passos (2009)
The study presents a panorama of the history of Religious Teaching in Brazil, starting from a bibliographical research and from a research in documents of the Regional Office of Education of Guará II, Brasília, Federal District, which specifically approach the Religious Teaching for students of the last grades of primary school. The study portrays the Religious Teaching in the new Lei de Diretrizes e Bases da Educação Nacional [Law of Guidelines and Bases of the National Education] (LDBEN), identifying in the analysis the need of execution of the article 33 in practice of Religious Teaching, trying to handle with the Parâmetros Curriculares Nacionais [National Curricular Parameters] (PCNs) of Religious Teaching, considering in its exercise the respect to cultural diversity in classroom, the human development and the formation of values in the individual and the phases that everyone passes until he or she arrives in a level of moral maturity. The study approaches the definition of values and the way as these values can be treated in the discipline of Religious Teaching in school context, having as base the four pillars of Education presented in the UNESCO s report. The study probes to reach the reality of students of the last grades of primary school of Guará II, in Brasília, Federal district. It concludes that it is possible to affirm that the education of values is present, even if implicit, in the respective discipline.